Measuring system of capillary rising damp in cement mortars. (March 2019) - Morón, Carlos; Ferrández, Daniel; Saiz, Pablo; Yedra, Engerst
Highlights: The new measuring equipment is able to detect variations of moisture by capillarity. The system is able to detect the variations of frequency due to the moisture. The mortar with mixed recycled aggregate presents higher water absorption coefficient. It becomes possible to create a profile of moistures in terms of time. Abstract: One of the most frequent pathologies in the building is an appearance of damp that impacts negatively the comfort and the health of users, undermining the state of the building. The study of the behaviour of materials in relation to water absorption can help to prevent and to diagnose the appearance of capillary damp in the building. This research proposes a measurement method that complements one proposed by the standard UNE-EN 1015-18, using a sensor able to measure the distribution of moisture in mortar samples. For that, two types of cement mortar were used: traditional mortar fabricated with natural aggregate and recycled mortar fabricated with 100% of mixed recycled aggregate. The new measuring equipment is able to detect variations of moisture due to the water absorption by capillarity in masonry mortars. According to the results, recycled mortars show higher water absorption by capillarity due to the larger capillary system formed in this type of mortar as a result of high absorption of recycled aggregates.